Conference on Lasers and Electro-Optics 2016
DOI: 10.1364/cleo_si.2016.stu1r.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nonlinear Susceptibility of Monolayer MoS2 using Second- and Third-Harmonic Generation Microscopy

Abstract: Abstract:Second-and third-harmonic generation microscopy of monolayer MoS 2 is reported for imaging and characterization of the material's nonlinearity. A telecommunication wavelength pump is used, revealing the material's promise for use in nonlinear optical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This technique, however, is limited to samples with an odd number of layers, as both bulk and even-layer-count few-layer crystals exhibit inversion symmetry; thus, second-order nonlinear effects are electric dipole forbidden. An attractive alternative is to harness third-harmonic generation (THG), which occurs irrespective of inversion symmetry [12,23,24]. Wang et al recently reported THG from MoS 2 thin films of 7-15 atomic layers [21], suggesting THG could provide complementary information in multiphoton microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, however, is limited to samples with an odd number of layers, as both bulk and even-layer-count few-layer crystals exhibit inversion symmetry; thus, second-order nonlinear effects are electric dipole forbidden. An attractive alternative is to harness third-harmonic generation (THG), which occurs irrespective of inversion symmetry [12,23,24]. Wang et al recently reported THG from MoS 2 thin films of 7-15 atomic layers [21], suggesting THG could provide complementary information in multiphoton microscopy.…”
Section: Introductionmentioning
confidence: 99%